Penentuan Logam Cr(VI) Menggunakan Metoda Voltammetri Stripping Anoda (VSA) pada Sampel Air Laut dan Air Sungai - Hilfi Pardi; Nancy Willian (Al-Kimia, 2022)
The research aims to determine Cr(VI) in the sea and river water samples using the Stripping Anode Voltammetry (VSA) method has been carried out by finding the optimum conditions for deposition potential, deposition time, pH, and electrolyte concentration measurements. As well as looking at the accuracy and accuracy of the method, it is necessary to determine the value of the relative standard deviation (SRD) and the value of recovery. The results obtained were -1.3 V deposition potential, 60 seconds deposition time, 0.2 M NH4Cl supporting electrolyte solution concentration, pH 10, SDR value was 2.36%, and the percent recovery value was 99.91%. As an application of this method, the determination of Cr(VI) was carried out in seawater samples from Senggarang and water from the Carang Tanjungpinang river. The concentration of Cr(VI) in Senggarang seawater samples was 133.751 g/L and in Carang River water samples 34,702 g/L.